The Application of Practice Rehearsal Pairs Learning Model toward Basic Programming Learning Outcomes - Uska, Muhammad Zamroni (Universitas Hamzanwadi, 2017)
Learning model is a general pattern of learning behavior to achieve conducive and effective learning goals. The PRP (Practice Rehearsal Pairs) model is one of the effective learning models used in this study. The purpose of this study was to determine the effect of PRP learning models on student learning outcomes in basic programming subjects. This type of research is quantitative research using quasi experimental design carried out atÂ Hamzanwadi University. The design in this study uses posttest only control group design with a total population of 54 students and the number of samples taken using the saturated sampling method is 54 students. Data collection used learning outcomes tests. Data analysis used descriptive analysis and paired sample ttest. The results showed that the average value of learning outcomes in the RPS model was 75.07 higher the average value of learning outcomes on the contextual model was 70.37. Hypothesis test results show that ttestÂ (8,619)> ttableÂ (2,060) (significant with Ï <0.05). Thus, the conclusion of this study is that there is a significant effect of student learning outcomes after applying the PRP learning model.